Technical Efficiency of Gambir Farming in Lima Puluh Kota Regency, West Sumatra, Indonesia - Fauziah Fauziah; Hasnah Hasnah; Rusda Khairati (International Journal of Agricultural Sciences, 2020)
This study analyzes the factors influencing gambier productivity, analyzes the technical efficiency of gambier farming, and analyzes the factors affecting gambier farming's technical efficiency. This research was conducted in Lima Puluh Kota Regency, a gambier production center in West Sumatra. Data were analyzed using the Cobb Douglas stochastic frontier production function. The results showed that the factors that significantly influenced gambier's productivity were labor, NPK fertilizer, plant age, number of trees, varieties, and technology. The number of labor, fertilizer factor, plant age, number of trees, and seedling varieties had a positive effect on gambier productivity. In contrast, NPK fertilizer and technology had a negative impact on gambier productivity. The technical efficiency level of gambier farming started from 0.25 to 0.99 with an average level of 0.76. It means that farmers are technically efficient but can still increase gambier productivity if they use production inputs appropriately and adequately. Factors that significantly influence technical efficiency are age, farming experience, and technology. Older farmers will have a higher level of technical efficiency compared to young age. The lower the farming experience, the more technically efficient the farmer is. Farmers who use the hydraulic jack system technology are more efficient than farmers who use the jack system technology